2017
DOI: 10.5089/9781475586213.001
|View full text |Cite
|
Sign up to set email alerts
|

Labor Force Participation in Chile: Recent Trends, Drivers, and Prospects

Abstract: Gains in labor force participation rates in Chile have slowed in recent years. We examine their determinants using a cohort-model analysis. Allowing for both age-and cohort-specific effects in the context of a seemingly unrelated regression equations (SURE) approach, we find that age factors play an important role in determining participation decisions, especially for males. For females, we find that strong positive time trends dominate the downward pressure from demographics, although those trends have recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
5
0
1
Order By: Relevance
“…The following variables are used to predict female labor force participation rates: year fixed effects; age-group dummies; three dummies for an individual's highest level of educational attainment (less than secondary, secondary, and higher than secondary education); a dummy for being married; rural dummy, region fixed effects, three dummies for a father's highest level of educational attainment, three dummies for a mother's highest level of educational attainment (less than intermediate, intermediate Figure III.5 shows that Egypt's and Jordan's FLFP rates follow an inverted U-shape curve with respect to age, peaking at around 40-45 years in Egypt and around 30-35 in Jordan. These results are in line with Blagrave and Santoro (2017), who use data from Chile and find that labor force participation is low for youth, increases during prime age, and decreases again as retirement approaches. They find that both male and female labor force participation rates follow these patterns in Chile; however, they find a gender gap that persists along the entire life cycle.…”
Section: Iii2 Female Labor-force Participation: a Generational Issuesupporting
confidence: 91%
“…The following variables are used to predict female labor force participation rates: year fixed effects; age-group dummies; three dummies for an individual's highest level of educational attainment (less than secondary, secondary, and higher than secondary education); a dummy for being married; rural dummy, region fixed effects, three dummies for a father's highest level of educational attainment, three dummies for a mother's highest level of educational attainment (less than intermediate, intermediate Figure III.5 shows that Egypt's and Jordan's FLFP rates follow an inverted U-shape curve with respect to age, peaking at around 40-45 years in Egypt and around 30-35 in Jordan. These results are in line with Blagrave and Santoro (2017), who use data from Chile and find that labor force participation is low for youth, increases during prime age, and decreases again as retirement approaches. They find that both male and female labor force participation rates follow these patterns in Chile; however, they find a gender gap that persists along the entire life cycle.…”
Section: Iii2 Female Labor-force Participation: a Generational Issuesupporting
confidence: 91%
“…Similar to Aaronson et al (2014) and Balleer et al (2014), we apply the logistic transformation to the LFPR to account for the fact that rates are bounded between 0 and 100. Also, we run the analysis using a log transformation as in Fallick and Pingle (2007) and Blagrave and Santoro (2017). Second, we replace the output gap with, alternatively, the unemployment rate and the unemployment gap.…”
Section: Robustnessmentioning
confidence: 99%
“…Studies (see Balleer, Gómez-Salvador & Turunen, 2009;Cai, 2009;Dayıoğlu & Kirdar, 2010;Luque, 2013;AaronSon et al, 2014;Reddy, 2016;Blagrave & Santoro, 2017;Chistobaev et al, 2018;Bernardi 2019) have shown that there are various areas to focus on when examining labor force participation rate. For instance, the textile sector, life cycles, marital status, and the number of children (Dayıoğlu & Kirdar, 2010;Luque, 2013), labor market slack (AaronSon et al, 2014), age and cohort effect (Balleer, Gómez-Salvador & Turunen, 2009), health status (Cai, 2009), ageing (Reddy, 2016;Blagrave & Santoro, 2017), health expenditures, gross capital formation, mortality rate, secondary school enrolment, life expectancy (Mushtaq, Mohsin, & Zaman, 2013), structural transformation, education and real wage (Mehrotra & Parida, 2017), unemployment rate, gross domestic product per capita, fertility rate (Taşseven, Altaş, & Ün, 2016) and life expectancy (Rechel, Doyle, Grundy & McKee, 2009). Further to that, women-related issues can also contribute to an increase in labor force participation, for example, female education, sectoral employment share, unemployment rate, wages, marital status (Fatima & Sultana, 2009), poverty and women workers (Azid, Khan & Alamasi, 2010), and unemployment rate for females (Özerkek, 2014).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%